2017
DOI: 10.1242/dev.153114
|View full text |Cite
|
Sign up to set email alerts
|

Inter-organ regulation of Drosophila intestinal stem cell proliferation by a hybrid organ boundary zone

Abstract: The molecular identities and regulation of cells at interorgan boundaries are often unclear, despite the increasingly appreciated role of organ boundaries in disease. Using as a model, we here show that a specific population of adult midgut organ-boundary intestinal stem cells (OB-ISCs) is regulated by the neighboring hindgut, a developmentally distinct organ. This distinct OB-ISC control occurs through proximity to a specialized transition zone between the endodermal midgut and ectodermal hindgut that shares … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 19 publications
(67 citation statements)
references
References 53 publications
4
62
0
Order By: Relevance
“…Other regions of the gut are maintained and repaired in different ways. The hindgut lacks specialized stem cells and following damage is maintained primarily by induced polyploidization of post-mitotic epithelial cells (Cohen et al, 2018;Fox and Spradling, 2009;Losick et al, 2013;Sawyer et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Other regions of the gut are maintained and repaired in different ways. The hindgut lacks specialized stem cells and following damage is maintained primarily by induced polyploidization of post-mitotic epithelial cells (Cohen et al, 2018;Fox and Spradling, 2009;Losick et al, 2013;Sawyer et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To distinguish between these two models, we acutely injured the larval hindgut and assessed whole-animal development progression (Methods). For tissue injury, we used the temporally and spatially regulated Gal4-UAS expression system, driven by a hindgut-specific enhancer of the brachyenteron (byn) gene to induce the apoptotic genes head involution defective (hid) and reaper (rpr) (Cohen et al, 2018;Fox and Spradling, 2009;Losick et al, 2013;Sawyer et al, 2017;Smith-Bolton et al, 2009). We induced injury at either the 2 nd or early 3 rd larval instar (L2-L3) stages or at the wandering third instar (hereafter L3W) stage.…”
Section: The Drosophila Hindgut Can Regenerate Without Delaying Metammentioning
confidence: 99%
“…We assayed cell death, cell number, and the frequency of pyloric cells with the mitotic marker Phospho-Histone H3 (PH3, Methods) during We next identified the number of additional mitotic cell cycles that the L3W pylorus must undergo following injury to produce the expanded adult pylorus and also the adult ileum. In the absence of injury, our previous lineage tracing experiments identified that L3W pyloric cells destined to produce the adult pylorus undergo approximately 2-3 divisions (yielding 5-6 cell clones in adults), whereas pyloric cells destined to generate the adult ileum undergo one division to make up the adult ileum (yielding 2 cell clones in adults) (Cohen et al, 2018;Fox and Spradling, 2009;Sawyer et al, 2017). In the presence of injury, our lineage tracing following L3W injury indicated a 3-fold increase in recovered adult pyloric clone size (from 5-6 cells to ~16 cells) and a doubling of ileal clone size (from 2 cells to 4 cells, Cohen et al, 2018).…”
Section: The Drosophila Hindgut Can Regenerate Without Delaying Metammentioning
confidence: 99%
See 2 more Smart Citations